-2(-7+4k)+9=-13

Simple and best practice solution for -2(-7+4k)+9=-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(-7+4k)+9=-13 equation:


Simplifying
-2(-7 + 4k) + 9 = -13
(-7 * -2 + 4k * -2) + 9 = -13
(14 + -8k) + 9 = -13

Reorder the terms:
14 + 9 + -8k = -13

Combine like terms: 14 + 9 = 23
23 + -8k = -13

Solving
23 + -8k = -13

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-23' to each side of the equation.
23 + -23 + -8k = -13 + -23

Combine like terms: 23 + -23 = 0
0 + -8k = -13 + -23
-8k = -13 + -23

Combine like terms: -13 + -23 = -36
-8k = -36

Divide each side by '-8'.
k = 4.5

Simplifying
k = 4.5

See similar equations:

| 24a/28a^2 | | 2x+1+4x=7 | | 240=8v+8b | | x/12=5-7 | | (2x-2)+45=180 | | k=2/5x | | ms+me=x | | y=4800-300(x-4.50) | | k=2/5 | | (n+8)(n+3)= | | Sin28=16/x | | 3x^2-120x+300=0 | | 8(x-1)+6(2-x)=8x | | k=9.92/12.8 | | -432=-8(-2-7n) | | Y=6x-44 | | 8c+5=5c-11 | | 4(12+6w+w)-3= | | 7.4-b=6.8 | | 3f=45 | | -15+8x=x | | y-(y+2)=7-(2y+1) | | -7=1-2y | | X^2-39=10 | | 4x^3/3y | | 8×2/3= | | 2(x+5)+2x=50 | | 6=10+2x | | 4=3x+39 | | 2m+6m=102 | | 13t+10=-65 | | X+4(X+6)=1 |

Equations solver categories